2021
DOI: 10.1136/bmjresp-2021-000911
|View full text |Cite
|
Sign up to set email alerts
|

Improving the early identification of COVID-19 pneumonia: a narrative review

Abstract: Delayed presentation of COVID-19 pneumonia increases the risk of mortality and need for high-intensity healthcare. Conversely, early identification of COVID-19 pneumonia grants an opportunity to intervene early and thus prevent more complicated, protracted and less successful hospital admissions. To improve the earlier detection of COVID-19 pneumonia in the community we provide a narrative review of current evidence examining the clinical parameters associated with early disease progression. Through an evolvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…We are also aware that the absence of standardised reporting protocols for HFNC use can lead to sources of bias that are difficult to account for based on the extant literature. For example, few studies report at which point from onset of COVID-19 illness that the patient presented (which is potentially important as patient presenting very late or very early could have a different disease course [ 51 53 ]). Other sources of heterogeneity include the definition of HFNC failure, where some studies reported a composite outcome including mortality, on top of the need for intubation or mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…We are also aware that the absence of standardised reporting protocols for HFNC use can lead to sources of bias that are difficult to account for based on the extant literature. For example, few studies report at which point from onset of COVID-19 illness that the patient presented (which is potentially important as patient presenting very late or very early could have a different disease course [ 51 53 ]). Other sources of heterogeneity include the definition of HFNC failure, where some studies reported a composite outcome including mortality, on top of the need for intubation or mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…However, although risk stratification protocols have been developed [ 11 ], potential diagnostic and prognostic tools are mostly based on relatively expensive and in many scenarios, difficult-to-access imaging methods (radiography, ultrasound, computed tomography (CT)) [ 12 , 13 ]. There is a clinical need for a simpler and more widely available prognostic tool that would enable healthcare providers to identify patients who have developed or are at risk of developing a severe disease, thereby facilitating triaging of patients and early intervention even at a patient's home or primary care centres [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous articles have attempted to summarize and delineate symptoms according to the severity of the SARS-CoV-2 disease [ 4 , 5 , 6 ]. Most COVID-19 patients present a self-limiting viral infection with cough, sore throat, headache, myalgia, fever, and other cold or flu symptoms.…”
Section: Introductionmentioning
confidence: 99%